Impact of Workplace Resilience and Team Cohesion on Reducing Workplace Stress: A Cross-Sectional Study - William, Erwin A. (Journal of Personality and Psychosomatic Research (JPPR), 2025)
This study aims to investigate the relationships between workplace stress, workplace resilience, and team cohesion. The primary objective is to determine the extent to which workplace resilience and team cohesion predict workplace stress among employees in various industries. A cross-sectional design was employed, involving 299 participants recruited from diverse occupational backgrounds. Data were collected using standardized self-administered questionnaires, including the Job Stress Survey (JSS), Connor-Davidson Resilience Scale (CD-RISC), and Group Environment Questionnaire (GEQ). Descriptive statistics were computed for all variables. Pearson correlation analysis was performed to examine the bivariate relationships between workplace stress and each independent variable. Multiple regression analysis was conducted to determine the predictive roles of workplace resilience and team cohesion on workplace stress. All analyses were performed using SPSS version 27. Descriptive statistics revealed mean scores of 45.23 (SD = 8.71) for workplace stress, 74.56 (SD = 10.32) for workplace resilience, and 68.91 (SD = 9.45) for team cohesion. Pearson correlation analysis indicated significant negative correlations between workplace stress and both workplace resilience (r = -0.63, p < .001) and team cohesion (r = -0.56, p < .001). The regression model was significant (F(2, 296) = 145.36, p < .001), with an R² of 0.50. Workplace resilience (B = -0.45, p < .001) and team cohesion (B = -0.38, p < .001) were significant predictors of workplace stress, indicating that higher resilience and cohesion are associated with lower stress levels. The findings suggest that workplace resilience and team cohesion significantly contribute to reducing workplace stress. Enhancing these factors through targeted interventions can help mitigate stress and improve employee well-being. Organizations should consider implementing resilience training programs and fostering a supportive team environment to promote a healthier, more productive workforce.